Caregiver Distress and Coronary Artery Disease: Prevalence, Risk, Outcomes, and Management - Bouchard, Karen; Dans, Michael; Higdon, Gloria; Quinlan, Bonnie; Tulloch, Heather (Current cardiology reports, 2022)
Purpose of Review Caregivers of patients with coronary artery disease (CAD) are integral to the health care system and contribute substantially to patients’ management. The purpose of this review is to provide a narrative synthesis of existing research on caregiving for patients who experienced an acute coronary syndrome (MI/unstable angina) and/or coronary revascularization (PCI/CABG). Recent Findings Thirty-one articles are included in this review. Overall, caregiver distress is low to moderate, ranging from 6 to 67% of caregivers, and seems to dissipate over time for most caregivers. Interventions have demonstrated success in reducing the distress of caregivers of patients with CAD. Due to the heterogeneity in study samples, measurements used, and timing of assessments and programming, these results are far from definitive. Summary Although evidence is accumulating, further advancement in caregiving science and clinical care is required to adequately understand and respond to the needs of caregivers throughout the patient’s illness trajectory.